Detection of Malingering during Head Injury Litigation - Reynolds, Cecil R.; Horton, Jr., Arthur MacNeill; SpringerLink (Online service) (Boston, MA : Springer US, 2012)
Increased public awareness of traumatic brain injuries has fueled a number of significant developments: on the one hand, more funding and more research related to these injuries and their resulting deficits; on the other, the possibility of higher stakes in personal injury suits - and more reasons for individuals to feign injury. Expanding both the conceptual and clinical knowledge base on the subject, the second edition of Detection of Malingering during Head Injury Litigation offers the latest detection tools and techniques for veteran and novice alike. As in its incarnation, this practical revision demonstrates how to combine clinical expertise, carefully-gathered data, and the use of actuarial models as well as common sense in making sound evaluations and reducing ambiguous results. And, the book navigates the reader through the many caveats that come with the job, beginning with the scenario that an individual may be malingering despite having an actual brain injury. Professional neuropsychologists and forensic psychologists will appreciate this new edition of Detection of Malingering during Head Injury Litigation as an invaluable source of refinements to their craft, and improvement as an expert witness.
Chapter 1 -- Assessment of Malingering and Falsification: Part one, Pushing to the Boundaries of Knowledge and Clinical Practice-Conceptual Issues -- Chapter 2. Assessment of Malingering and Falsification: Part two, Pushing the Boundaries of Knowledge and Clinical Practice-Clinical Application -- Chapter 3. Noncredible Performance in Mild Head Injury -- Chapter 4. Detection of Malingering Using Forced-Choice Techniques -- Chapter 5. Fractitious Responding and Malingered Memory Disorder -- Chapter 6. Performance on the WMT, MSVT & NV-MSVT in Children with Developmental Disabilities and in Adults with Mild Traumatic Brain Injury -- Chapter 7. Detecting Malingering on the Luria-Nebraska Neuropsychological Battery -- Chapter 8. Detection of Malingering and Invalid Test Results Using the Halstead-Reitan Battery -- Chapter 9. Detection of Feigning of Head Injury Symptoms on the MMPI-2 -- Chapter 10. Explaining Symptom Validity Testing to the Trier of Fact -- Chapter 11. Distinguishing Genuine from Malingered Posttraumatic Stress Disorder in Head Injury Litigation -- Chapter 12. Clinical Detection of Malingering -- Chapter 13. Clinical Acumen, Common Sense, and Data Based Decision Making: Actuarialism in the Detection of Dissimulation During Head Injury Litigation -- Index.
Keywords: Philosophy (General).; Psychiatry; Psychology, clinical; Law -- Psychological aspects; Psychology; Neuropsychology; Psychiatry; Law and Psychology